A Thin Line Between DOOR & TRAP: Why (Neo-)Liberal Trans* In_Visibility Matters: Trans Cultural Porduction and the Politics of Visibility (KULT_online, 2018)
As the recently published anthology Trap Door. Trans Cultural Production and the Politics of Visibility shows quite plainly, social change and the formation of subjectivity are still closely linked to questions of visibility. These have always acted as a battleground that allows expression of different perceptions, norms, and knowledges about categories of difference. Focusing on the current moment when trans* people appear to be winning the struggle for visibility while also continuing to be subject to psychological and physical violence on a daily basis, the 21 inter- and transdisciplinary contributions from mostly trans* and queer scholars, artists and activists of color open ‘new doors’ for thinking carefully about the ethical question of anti-discriminatory politics of trans* visibility. Therefore, this is a long overdue and essential companion for everyone who is interested in ethics of visuality.